Ablative radiotherapy for liver tumors using stereotactic MRI-guidance: A prospective phase I trial. (May 2022) - van Dams, Ritchell; Wu, Trudy C.; Kishan, Amar U.; Raldow, Ann C.; Chu, Fang-I; Hernandez, Jackie; Cao, Minsong; Lamb, James M.; Mikaeilian, Argin; Low, Daniel A.; Steinberg, Michael L.; Lee, Percy
Highlights: SBRT using MR-Co is a safe and feasible option for treatment of liver tumors with ablative doses. 2-year LC with MRgRT is comparable to prior series using a conventional CT-guided linear accelerator. A difference in LC between number of lesions (single vs. multiple) and BED (< or ≥100 Gy) was observed. MR-guided SBRT is very well tolerated without any acute grade 3 toxicities. V35Gy < 0.35 cc to individual loops of small bowel should be recognized as a dose constraint for 3-fx SBRT. Abstract: Background and purpose: To prospectively determine the feasibility, safety, and efficacy of stereotactic body radiation therapy (SBRT) to primary and secondary liver tumors with MR-guided radiation therapy (MRgRT). Materials and methods: Treatment plans with a conventional CT-guided linear accelerator and a MRI-guided tri- 60 Co teletherapy unit (MR-Co) were generated and compared for patients undergoing liver-directed SBRT from 2015 to 2017. If dosimetric parameters were met on MR-Co, patients were treated with MRgRT. The highest priority constraint was >1000 cc or >800 cc of normal liver receiving <15 Gy for single- or multiple-lesion treatments, respectively. Treatment was delivered every other day. Results: Of 23 patients screened, 20 patients (8 primary, 12 secondary) and 25 liver tumors underwent MR-guided SBRT to a median dose of 54 Gy (range 11.5–60) in a median of 3 fractions (range 1–5). With a median follow up of 18.9 months, the 1- and 2-year estimate of local control were 94.7% and 79.6%, respectively. A difference in local control between single and multiple lesions or BED ≥ 100 Gy10 and BED < 100 Gy10, respectively, was observed. The 2-year estimate of overall survival (OS) was 50.7% with a median OS of 29 months. There were no acute grade ≥ 3 toxicities and one late grade 3/4 toxicity from a single patient whose plan exceeded an unrecognized dose constraint at the time. Conclusion: MR-guided SBRT is a viable and safe option in the delivery of ultrahypofractionated ablative radiation treatment to primary and secondary liver tumors resulting in high rates of local control and very favorable toxicity profiles.